Increased body mass index linked to greater short- and long-term survival in sepsis patients: A retrospective analysis of a large clinical database. (October 2019) - Li, Shuhe; Hu, Xiaoguang; Xu, Jinghong; Huang, Fa; Guo, Zilu; Tong, Li; Lui, Ka Yin; Cao, Lu; Zhu, Yanping; Yao, Jiyou; Lin, Xiaobin; Guan, Xiangdong; et al.
Highlights: Overweight and obese patients had greater survival benefits at 30 days and 1 year. Underweight patients tended to have higher mortality risk. Obese patients were shown to experience more aggressive treatments. Obesity was associated with longer ventilation, ICU and hospitalization duration. Abstract: Objectives: We investigated the impact of obesity (proxied as body mass index (BMI)), on short- and long-term mortality in sepsis patients. Methods: We conducted a retrospective analysis with adult sepsis ICU patients in a US medical institution from 2001 to 2012 in the MIMIC-III database. The WHO BMI categories were used. Multivariate logistic regression assessed the relationships between BMI and 30-day and 1-year mortality. Results: In total, 5563 patients were enrolled. Obese patients tended to be younger (P < 0.001), to be female (P < 0.001), to acquire worse SOFA scores (P < 0.001), and to receive more aggressive treatment compared with their normal weight counterparts. Obese patients had notably longer mechanical ventilation periods and ICU and hospital lengths of stay (LOSs). In the final model, overweight and obese patients had lower 30-day (OR 0.77, 95% CI 0.66–0.91; OR 0.65, 95% CI 0.56–0.77, respectively) and 1-year (OR 0.83, 95% CI 0.71–0.96; OR 0.70, 95% CI 0.60–0.81, respectively) mortality risks than normal weight patients. In contrast, underweight patients had worse 30-day and 1-year outcomes compared with normal weight patients (P = 0.01, P < 0.001, respectively). In morbidly obese, severe sepsis and septic shock patients, obesity remained protective. Conclusions: Obesity was correlated with short- and long-term survival advantages in sepsis patients.